2019
DOI: 10.1371/journal.pone.0216449
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of rape and sexual violence in the platinum mining district of Rustenburg, South Africa: Prevalence, and factors associated with sexual violence

Abstract: Background Estimates for the prevalence of rape and other forms of sexual violence (SV) vary in South Africa. This survey aimed to provide clarity by quantifying the prevalence of SV (forced sex or sexual acts) by 1) sexual partners, and 2) non-partners, and to describe factors associated with these outcomes among women (18–49 years) living in Rustenburg Municipality. Materials and methods We conducted a cluster-randomized household survey (November—December 2015). Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
0
23
1
1
Order By: Relevance
“…The observed prevalence in this study is higher than the global prevalence of 7.2% [36] and a prevalence of 17.4% in Southern Africa [36]. Another study conducted in another South African Province reported a 24.9% lifetime prevalence of sexual violence among women aged 18-49 years [37]. Our reported prevalence is also higher than the 16.7% reported prevalence of sexual violence in the past year among Norwegian students [38].…”
Section: Discussioncontrasting
confidence: 66%
“…The observed prevalence in this study is higher than the global prevalence of 7.2% [36] and a prevalence of 17.4% in Southern Africa [36]. Another study conducted in another South African Province reported a 24.9% lifetime prevalence of sexual violence among women aged 18-49 years [37]. Our reported prevalence is also higher than the 16.7% reported prevalence of sexual violence in the past year among Norwegian students [38].…”
Section: Discussioncontrasting
confidence: 66%
“…Sexual assault (SA), including rape, is a human rights violation with extensive negative health consequences. 15 In this study, sexual assaults constituted 3.4% of all gynecological cases in our center. This finding is comparable to the reports made by Adeleke et al in Oshogbo and by Badejoko et al in Ile-Ife.…”
Section: Discussionmentioning
confidence: 63%
“…20 Furthermore, the higher the number of the denominator used, the lower the prevalence and viceversa or may be due to actual differences across locations and/or methodological differences. 3,4,15 It could also be due to stigma associated with sexual violence that prevent persons assaulted from reporting. 3 In this study, younger age (79.3%) less than 20, with the ages ranging from 3 to 37 years and a mean of 14.1±7.8 years formed the majority of the victims of the sexual assault.…”
Section: % Documented By Ezechi Et Al Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have linked sexual violence to increased risk of HIV infection [34,35], poor mental health outcomes [36,37], poor self-rated health [37] and non-use of contraceptives [35], we did not nd any study examining the link between the experience of sexual violence and unintended pregnancy among adolescent and AGYW in South Africa. This is the case despite the reported high prevalence of sexual violence in the country [37][38][39][40]. As such, the main research question this study examines is: what is the link between sexual violence and unintended pregnancy among AGYW?…”
Section: Introductionmentioning
confidence: 96%